2021
DOI: 10.1177/0734242x211042276
|View full text |Cite
|
Sign up to set email alerts
|

Data mining and knowledge discovery in databases for urban solid waste management: A scientific literature review

Abstract: The processes related to solid waste management (SWM) are being revised as new technologies emerge and are applied in the area to achieve greater environmental, social and economic sustainability for society. To achieve our goal, two robust review protocols (Population, Intervention, Comparison, Outcome, and Context (PICOC) and Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA)) were used to systematically analyze 62 documents extracted from the Web of Science database to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 80 publications
0
11
0
1
Order By: Relevance
“…32 The ISI Web of Science Core Collection database was searched for eligible publications, as it has a large number of research documents from high-impact journals. [33][34][35][36][37][38] The documents were exported on August 14, 2021. Quality assessment attributes are shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…32 The ISI Web of Science Core Collection database was searched for eligible publications, as it has a large number of research documents from high-impact journals. [33][34][35][36][37][38] The documents were exported on August 14, 2021. Quality assessment attributes are shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…SWMS-related knowledge can be categorized into three major components: the socioeconomic context of SWMS, the SWMS themselves, and the performance of SWMS. The regional socioeconomic context of SWMS consists of the general public (characterized by its demographics, lifestyles, and education/environmental awareness), regional economy, climate patterns, and governance (Abdallah et al, 2020;Beigl et al, 2008;Dias et al, 2021;Kolekar et al, 2016). The broader socioeconomic context of SWMS includes domestic and international trades, as well as markets for secondary and primary materials (Brooks et al, 2018;Das et al, 2019;Matter et al, 2015).…”
Section: Framework Of the Knowledge Basementioning
confidence: 99%
“…First, existing MSW data are mainly stored in "silos" confined by geographical boundaries or topical focuses (Cohen and Gil, 2021). There is not a single centralized repository to organize all the information in a systemic manner, which is verified by the lack of relevant peer-reviewed articles on multi-attribute MSW knowledge systems (Dias et al, 2021). Second, due to the financial and organizational costs of data collection, waste characterization studies are infrequently conducted or reported, especially in low-income countries (Kaza et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Para atender ao objetivo do estudo, realizou-se uma revisão sistemática da literatura, de cunho crítico-reflexivo, apoiada pelo protocolo PRISMA-P. A base de dados ISI Web of Science (WoS) Core Collection foi utilizada por se tratar de uma base de dados robusta com trabalhos de qualidade e revistas de alto fator de impacto indexadas (SEVERO et al, 2021;KOLLING et al, 2021;DIAS et al, 2021;SOTT et al, 2022). Foram selecionadas apenas revisões da literatura, bibliometrias e mapeamentos científicos do campo de estudo, a fim de refinar as buscas, considerando que os estudos dos tipos selecionados devem ser completos e abrangentes por já terem revisado a literatura previamente.…”
Section: Procedimentos Metodológicosunclassified